Electrical and colloidal properties of hydrogenated nanodiamonds: Effects of structure, composition and size - Stepan Stehlik; Ondrej Szabo; Ekaterina Shagieva; Daria Miliaieva; Alexander Kromka; Zuzana Nemeckova; Jiri Henych; Jan Kozempel; Evgeny Ekimov; Bohuslav Rezek (Carbon Trends, 2024)
Hydrogenated nanodiamonds (NDs) get increasing attention as promising nanomaterial in biology as well as optoelectronics. This study shows how the ND synthesis process and ND size are reflected in their different colloidal/hydration and electronic properties. We employ three different ND types: detonation ND (DND), top-down high-pressure high-temperature ND (TD_HPHT ND) prepared by milling of HPHT monocrystals, and bottom-up high-pressure high-temperature ND (BU_HPHT ND) prepared by HPHT synthesis from chloroadamantane. Zeta potential measurements and Fourier transform infrared spectroscopy analysis (FTIR) reveal the best colloidal stability in neutral to basic pH and the strongest affinity to water for DND. Electrical and FTIR measurements connected with an annealing treatment show a steep increase of electrical conductivity in BU_HPHT ND above 2 nm and reveal different contribution of transfer doping in BU_HPHT ND and TD_HPHT ND despite similar conductivity values (≈ 10−5 S.cm−1). We also confirm the correlation of the ND conductivity with IR transmission at the phonon frequency of the diamond (1330 cm−1). Neutron irradiation of a TD_HPHT ND corroborates the crucial role of structural defects in the above colloidal and electronic properties of hydrogenated nanodiamonds.